1988
DOI: 10.1002/mrd.1120200209
|View full text |Cite
|
Sign up to set email alerts
|

Identification of sterol acceptors that stimulate cholesterol efflux from human spermatozoa during in vitro capacitation

Abstract: The nature of cholesterol-binding proteins acting upon human spermatozoa during in vitro capacitation was determined by measuring the efflux of [3H]cholesterol and of [3H]cholesteryl sulfate from labeled spermatozoa. Efflux of [3H]sterols was stimulated when the labeled gametes were incubated in Ham's F-10 medium supplemented with female serum or follicular fluid. Upon centrifugation of capacitated spermatozoa and application of the supernatant to density-gradient ultracentrifugation for lipoprotein analysis, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
90
2
3

Year Published

1990
1990
2012
2012

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 158 publications
(104 citation statements)
references
References 35 publications
6
90
2
3
Order By: Relevance
“…The fact that FF is in vitro the best capaciting agent ( 8 ) can be explained, at least in part, by the presence of cholesterol acceptors, such as HDL and albumin, that we and others found out ( 10,13,33 ). Moreover, we evidenced that HDL is the single class of lipoprotein during the preovulatory period ( 13 ) and that pre ␤ HDLs represent about 18% of total HDL of the FF ( 14 ).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…The fact that FF is in vitro the best capaciting agent ( 8 ) can be explained, at least in part, by the presence of cholesterol acceptors, such as HDL and albumin, that we and others found out ( 10,13,33 ). Moreover, we evidenced that HDL is the single class of lipoprotein during the preovulatory period ( 13 ) and that pre ␤ HDLs represent about 18% of total HDL of the FF ( 14 ).…”
Section: Discussionsupporting
confidence: 52%
“…We fi rst evaluated the effects of varying FF concentrations (5,10,20,30,40, and 50%, v/v in modifi ed B2 medium) on spermatozoa hyperactivation process after 5 min of incubation at 37°C ( Fig. 1A ).…”
Section: Effects Of Ff or Hdl On Kinetics Of Spermatozoa Hyperactivationmentioning
confidence: 99%
“…In mammals newly ejaculated sperm is inactive and needs to be capacitated by several factors (Chang, 1951;Austin, 1952). It is well established that cholesterol efflux plays an important role in the capacitation of mammalian sperm (Langlais et al, 1988). This efflux triggers a signaling cascade that includes phosphorylation of several sperm proteins and elevation of Ca 2ϩ concentration (Visconti et al, 1999).…”
Section: Enrichment Of Cholesterol In Germ Line Cellsmentioning
confidence: 99%
“…Following the release of these decapacitation factors, spermatozoa experience a dramatic efflux of cholesterol from the plasma membrane (Davis, 1981). This efflux appears to be driven by active sequestration upon exposure of the spermatozoa to an environment rich in appropriate cholesterol sinks (Davis, et al, 1979, Langlais, et al, 1988, Visconti, et al, 1999, and accounts for a striking increase in membrane fluidity. Bovine serum albumin is commonly used within in vitro capacitating media as a cholesterol acceptor, although analogous acceptor(s) are believed to be present within the female reproductive tract.…”
Section: Capacitationmentioning
confidence: 99%
“…Bovine serum albumin is commonly used within in vitro capacitating media as a cholesterol acceptor, although analogous acceptor(s) are believed to be present within the female reproductive tract. Indeed, studies of human follicular fluid have identified the presence high concentrations of albumin and other cholesterol sinks (Langlais, et al, 1988). Cholesterol efflux from the plasma membrane has also been correlated with an influx of bicarbonate ions (HCO3 -) into the cell (Boatman and Robbins, 1991, Chen, et al, 2000, Garty and Salomon, 1987, Okamura, et al, 1985.…”
Section: Capacitationmentioning
confidence: 99%